Determinación de la fuerza cortante necesaria para seccionar llantas usadas (2024)
Currently, great interest has been taken in the reuse of tires due to their negative environmental impact, since they do not decompose and emit greenhouse gases such as methane. According to the International Union for Conservation of Nature, tires represent 28% of the micro plastic waste in the oceans [20].